Analysis and Forecasting Students’ Academic Performance Using a Digital Educational Environment - A. E. Shukhman; D. I. Parfenov; L. L. Legashev; L. S. Grishina (Высшее образование в России)
Analysis and Forecasting Students’ Academic Performance Using a Digital Educational Environment The article discusses technical solutions used at Orenburg State University to organize a digital educational environment. Also, the authors have studied the academic performance of technical and humanities students during the period of face-to-face education and during the lockdown period. The analysis of academic performance shows the absence of significant deviations in one direction or another. The key internal and external factors that influence the students’ academic performance are highlighted. It can be concluded that the use of both internal and external factors gives a high accuracy in predicting the final progress of students.